Structural reliability analysis of a submerged floating tunnel under copula-based traffic load simulations. (15th October 2022) - Torres-Alves, G.A.; 't Hart, C.M.P.; Morales-Nápoles, O.; Jonkman, S.N.
Abstract: A submerged floating tunnel (SFT) is a structure that has been proposed as an innovative solution for waterway crossings around the world. However, to this day, no SFT has been constructed yet. One of the main reasons is that there is an insufficient insight into the structural reliability of the SFT. Here, a method to assess the expected structural response of an SFT under traffic loads and a reliability assessment of the results is presented. To do this, traffic models and structural response and reliability are coupled. The methodology presented herein proposes an innovative way to combine copula-based models and structural models to obtain more a more realistic structural response of the SFT. The focus will be on one failure mechanism, leakage caused by bending failure of the SFT in the longitudinal direction. The method utilizes a copula-based model to characterize the traffic loads and simulate traffic loads on the SFT (axle weight, inter-axle distance, and inter-vehicle distance). Next, a structural model is used to assess the structural response and derive stresses. Using a probabilistic analysis, the design of the cross-section can be adapted so that it meets the requirements for leakage caused by bending moments. For the case study is demonstrated that for a buoyancy weight ratio (BWR) of 1.1 an optimal design can be achieved based on a probabilistic method. This methodology could be extended to other failure modes of an SFT or to other structures. Highlights: The structural response of Submerged Floating Tunnels due to traffic loads. Application of copulas to define a representative load sequence. Application of low level Finite Elements Method to calculate the structural response. Design optimization by use of probabilistic tools.